The Impact of COVID-19 Pandemic on the E-Government Development and on The Reduction of Digital Exclusion - Magdalena FRAŃCZUK; Aldona PIOTROWSKA (Communications of International Proceedings, 2021)
The paper is up-to-date, it focuses on an analysis of the impact of the pandemic crisis on the development of e-government, and on the reduction of digital exclusion, on the example of Poland. The crisis caused by the pandemic had an impact on the development of e-government services, causing need for rapid digitalization of the administration, i.e. in a shorter time than the deadlines assumed in the implementation of the EU directives in this area, there was a change in the way the administration (in particular administration providing services) operates. We observe - the increase in digital readiness of the society, - increase in digital competences and thus a decrease in digital exclusion. The analysis is based on a review of instruments which were applied in order to implement e-government in order to raise digital competences of officers and administration clients, as a reaction to a specific pandemic situation, in the context of the right to freedom from exclusion. In the light of the available statistics the pandemic crisis has influenced the development of public e-services and contributed to an increase in the digitalization of the administration. The deadlines for the expansion of the e-government system resulting from EU acts have not yet passed, while a satisfactory level of the development of the e-government sector in Poland has already been achieved. The lack of face-to-face contact in the customer-administration relationship meant that citizens had to adapt to the situation and move to virtual contact, thus increasing their digital readiness.
Keywords: public administration; digitalization; inclusion